2008
DOI: 10.1128/aem.01000-08
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation, Retention, and Depuration of Enteric Viruses by Crassostrea virginica and Crassostrea ariakensis Oysters

Abstract: Crassostrea ariakensis oysters are under review for introduction into the Chesapeake Bay. However, the human health implications of the introduction have not been fully addressed. This study evaluated rates of bioaccumulation, retention, and depuration of viruses by Crassostrea virginica and C. ariakensis when the two oyster species were maintained in separate tanks containing synthetic seawater of various salinities (8, 12, or 20 ppt). Oyster bioaccumulation tanks were seeded with 10 3 PFU/ml of hepatitis A v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 30 publications
6
57
0
Order By: Relevance
“…(Le Guyader et al, 2006;Mcleod et al, 2009aMcleod et al, , 2009bTian et al, 2006;Wang et al, 2008), (Maalouf et al, 2010;Nappier et al, 2008). Provost et al (2011) (hematocytes) (acidic digestion) .…”
Section: Real Time Rt-pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…(Le Guyader et al, 2006;Mcleod et al, 2009aMcleod et al, , 2009bTian et al, 2006;Wang et al, 2008), (Maalouf et al, 2010;Nappier et al, 2008). Provost et al (2011) (hematocytes) (acidic digestion) .…”
Section: Real Time Rt-pcrmentioning
confidence: 99%
“…Provost et al (2011) (hematocytes) (acidic digestion) . feline calicivirus murine norovirus (Mcleod et al, 2009b;Nappier et al, 2008;Provost et al, 2011;Ueki et al, 2007).…”
Section: Real Time Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological property of the shellfish tissues influences the pattern of accumulation of different pathogens observed in different shellfish species 16 . Several studies have shown that bioaccumulation of pathogens in shellfish (either experimentally under controlled conditions, or naturally in their growing waters) is dependent on a number of factors; including physiology of the shellfish and/or pathogen, the rate of metabolism in the shellfish, the duration of exposure of the shellfish to the pathogen or its source, the exposure dose, and other factors, such as salinity and temperature, that can also influence the filtration rate in the shellfish 5,12,13 . There appears to be a differential selection process involved in bioaccumulation, based on the size and shape of particles, which is influenced by the bioaccumulation efficiency of the shellfish species as well as the ability of the labial palp and gills to reject or filter certain particles 3,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Bivalves are also capable of ingesting a wide variety of pathogens (Silverman et al, 1995;Graczyk et al, 2003Graczyk et al, , 2006Proakis, 2003;Nappier et al, 2008). Given their ability to efficiently remove particles greater than 0.4 lm in diameter from water, bivalves may filter individual bacteria (0.5-2 lm) and FIG.…”
mentioning
confidence: 99%